1987
DOI: 10.1111/j.1467-8624.1987.tb01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Constraints: Black-White Differences in the Formation of Interracial Friendships

Abstract: In this article, we examine the effects of classroom characteristics on the interracial friendliness of students in desegregated classrooms. We argue that social psychological processes that affect cross-race sociability are set in motion by the classroom climate, the organization of instruction, and the class racial composition. The effects of these variables on the likelihood of cross-race friendships are observed in longitudinal data from 455 students in 16 fourth- through seventh-grade desegregated classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 9 publications
6
64
0
Order By: Relevance
“…Regardless of the specific interpretation, this scenario would suggest that minority children, and the majority-race children who choose them as friends, are peripheral, disenfranchised members of the peer group. This scenario has received some empirical support in an earlier study, in which popular students reportedly nominated fewer cross-race peers as friends than did less popular students (Hallinan & Teixeira, 1987b). More recent research has reported that numerical minorities in the classroom continue to be less socially accepted than their majority-race peers (e.g.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Regardless of the specific interpretation, this scenario would suggest that minority children, and the majority-race children who choose them as friends, are peripheral, disenfranchised members of the peer group. This scenario has received some empirical support in an earlier study, in which popular students reportedly nominated fewer cross-race peers as friends than did less popular students (Hallinan & Teixeira, 1987b). More recent research has reported that numerical minorities in the classroom continue to be less socially accepted than their majority-race peers (e.g.…”
mentioning
confidence: 81%
“…In the end, it may be that there are various processes at workand not one process can describe how and why all cross-race friendships arise. Such processes might include teaching practices, such as ability grouping and an emphasis on achievement versus enjoyment of learning (see Hallinan & Smith, 1985;Hallinan & Teixeira, 1987a, 1987b, as well as teacher reward for cross-race friendships (Cooper, Johnson, Johnson & Wilderson, 1980;Hauserman, Walen & Behling, 1973). Furthermore, as noted earlier, black children's focus may be on befriending other black children, due to the importance of such friends for developing an ethnic and self-identity (Hamm, 2000), rather than focusing on the exclusion of white children from their circle of friends.…”
Section: Speculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction generally leads to positive sentiment (Homans, 1950;Lawler, 1992;Ostrom, 1998), especially when in the context of conditions specified by contact theory, including working for a common goal and participating in equal status groups (Hallinan and Sorensen, 1985;Schofield, 1979). For example, primary and secondary school studies find that opportunities for cross-race interactions lead to increased interracial sociability and social ties among the children and youth (Hallinan and Teixeira, 1987;Hallinan and Williams, 1989;Joyner and Kao, 2000;Patchen, 1982;Schofield, 1978), and the effects are even more pronounced when integration occurs within school programs, classes, and educational tracks (such as college preparatory) (Hallinan and Williams, 1989).…”
Section: Contact Theory and Multiracial Social Tiesmentioning
confidence: 96%
“…Whether White or Black students have more cross-race friends often depends on availability (Clark & Ayers, 1992;Hallinan & Teixeira, 1987b;Howes & Wu, 1990;Shrum et al, 1988;Singleton & Asher, 1979). Two recent studies accounted for availability by using a ratio index of the number of friends of a given race divided by the number of available peers of that race.…”
Section: Same-and Cross-race Peer Relationsmentioning
confidence: 99%